Implementasi Kegiatan Perkusi dalam Meningkatkan Kemampuan Lobus Temporal Anak - Hasri, Partika Dwi; Juniarti, Siska; Sari, Tintri Nupita (Lembaga Yasin AlSys, 2024)
This article explores the impact of integrating percussion activities into children's learning environments to enhance temporal lobe abilities. The temporal lobe, crucial for auditory processing and memory, plays a significant role in language development, music appreciation and social interaction. By engaging children in rhythmic exercises, such as drumming, clapping and rhythm-based games, educators can stimulate temporal lobe functions, fostering improved language acquisition, cognitive skills and social-emotional development. This article reviews current research on the neurological benefits of music and percussion on the developing brain, highlighting the potential of percussion activities as a valuable tool in educational settings. Additionally, practical strategies and considerations for implementing percussion activities in classrooms are discussed, emphasizing the importance of creating inclusive and engaging learning experiences for all children.